PROBLEMS OF SOCIAL SCIENCES EDUCATION TEACHERS IN THE TEACHING AND LEARNING PROCESS IN SCHOOLS - Romi Mesra; Azwar Ananda (Labor Program Studi Pendidikan Sosiologi, 2023)
This research aims to find out the problems of social sciences education teachers in the teaching and learning process in schools. This research method is a qualitative method in the form of a literature study where the researcher collects information from various literature that is relevant to the researcher's research to then obtain findings in accordance with the research objectives. The results of this research indicate that the teacher's inability to apply learning methods and media that match the diversity of student characteristics in the classroom. Teacher-Centre Learning and Book Packages. The learning process is not in line with what was planned in the RPP. Teachers who teach social studies are not based on their skills. And lack of availability of facilities and infrastructure to support the success of social studies learning.